Strategy of teachers in suporting environmentally sustainable development - Wiwik Okta Susilawati; Hendro Widodo; Sumarno Sumarno (Intelektual Pustaka Media Utama, 2019)
This study aims to find out: 1) strategy of teachers in instilling character caring for the environment ; 2) successful instilling character caring for the environment; 3) supporting and inhibiting factors for instilling character caring for the environment. The research used in this study is qualitative research. The research subjects were headmaster, deputy headmaster, teachers, and students. Determination of the subject of the study was carried out by purposive sampling technique. The technique of data collection is done by using interview, observation and documentation methods. The type of data analysis uses the Miles and Huberman model, namely reduction, data display, and conclusion/data verification. 1) Strategy of teachers in instilling character through materials, methods, and implementation of tasks; 2) Successful instilling character attention can be seen from students who have been able to find answers to the assignments given by the teacher which make the students increase. 3) Supporting factors character development are teachers being role models, able to move other teachers to continue to accompany activities, teachers always appeal, teachers integrate the concept of environmental care in the RPP, syllabus and teaching and learning process. While the inhibiting factor of student character involvement is in the students themselves.